Effect of Water-Reducing Admixtures Having Hybrid Silicon Air-Entraining Surfactants on Some Properties of Concrete Mixtures - Emin, Ayvaz; Ozen, Suleyman; Mardani-Aghabaglou, Ali; Unlu, Ayda; Kapti, Tolga (Asce-Amer Soc Civil Engineers, 2022)
In order to improve the fresh properties and freeze-thaw resistance of cementitious systems, water-reducing and air-entraining admixtures are actively used in concrete mixtures. Generally, these mentioned admixtures are added to concrete mixtures as two separate admixtures. In this case, when the properties/compositions of one of the admixtures change, compatibility problems of admixtures may occur with each other or with the cement, and the fresh/hardened properties of the concrete may be adversely affected. In this study, a modified water-reducing admixture with both fluidity and air-entraining properties was produced. The utilization effect of high-range water-reducing admixtures (HRWR) having different ethylene oxide/propylene oxide (EO/PO)-based air-entraining surfactants (AES) on some properties of concrete mixtures was investigated. For this purpose, firstly, hybrid silicone AESs with a silicon content of 20%, 33%, and 38.5% were supplied. Then, HRWRs containing seven different AES were produced by using substitution and synthesis methods. In HRWRs produced by the substitution method, 3 and 5 wt. % of HRWR were substituted with EO/PO-based hybrid silicon AES. In the other method, EO/PO-based hybrid silicon air-entraining macromonomers were bonded to the HRWR at ratios of 1, 3, and 5 wt. % during its synthesis process. Replacing HRWR with hybrid silicone AESs increased admixture demand to provide the target slump value in concrete mixtures. Utilization of AESs containing 20% and 33% silicon in HRWR by the substitution method positively affected the permeability and compressive strength of concrete mixtures, while the rise of this ratio to 38.5% by using the synthesis method did not affect them significantly. The presence of surfactant with 20% silicon in 3% and 5% of the admixture and with 33% silicon in 5% of the admixture positively affected frost resistance of concrete mixtures. However, the use of surfactants with 33% silicon content in 3% of the admixture and 38.5% silicon in 1%, 3%, and 5% of the admixture showed a negative effect on the frost resistance of the mixtures.
Keywords: Air entraining surfactant (AES); Ethylene; propylene oxide; Water reducing admixture; Permeability; Freezing thawing